Mechanics of the muscles crossing the hip joint during sprint running - Nagano, Y.; Higashihara, A.; Takahashi, K.; Fukubayashi, T. (Journal of Sports Sciences, 2015)
We aimed to demonstrate the changes over time in the lengths and forces of the muscles crossing the hip joint during overground sprinting and investigate the relationships between muscle lengths and muscle-tendon unit forces - particularly peak biceps femoris force. We obtained three-dimensional kinematics during 1 running cycle from 8 healthy sprinters sprinting at maximum speed. Muscle lengths and muscle-tendon unit forces were calculated for the iliacus, rectus femoris, gluteus maximus, and biceps femoris muscles of the target leg as well as the contralateral iliacus and rectus femoris. Our results showed that during sprinting, the muscles crossing the hip joint demonstrate a stretch-shortening cycle and 1 or 2 peak forces. The timing of peak biceps femoris force, expressed as a percentage of the running cycle (mean [SD], 80.5 [2.9]%), was synchronous with those of the maximum biceps femoris length (82.8 [1.9]%) and peak forces of the gluteus maximus (83.8 [9.1]%), iliacus (81.1 [5.2]%), and contralateral iliacus (78.5 [5.8]%) and also that of the peak pelvic anterior tilt. The force of the biceps femoris appeared to be influenced by the actions of the muscles crossing the hip joint as well as by the pelvic anterior tilt.